Effect of COVID-19 on acute treatment of ST-segment elevation and Non-ST-segment elevation acute coronary syndrome in northwestern Switzerland. (February 2021) - Boeddinghaus, Jasper; Nestelberger, Thomas; Kaiser, Christoph; Twerenbold, Raphael; Fahrni, Gregor; Bingisser, Roland; Khanna, Nina; Tschudin-Sutter, Sarah; Widmer, Andreas; Jeger, Raban; Kaufmann, Beat; Pfister, Otmar; et al.
Abstract: Background: To investigate the effect of the corona virus disease 2019 (COVID-19) pandemic on the acute treatment of patients with ST-segment elevation (STEMI) and Non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Methods: We retrospectively identified patients presenting to the emergency department (ED) with suspected ACS. We evaluated the number of percutaneous coronary interventions (PCIs) for STEMI, NSTE-ACS, and elective PCI cases. In STEMI patients, we assessed the time from chest pain onset (cpo) to ED presentation, post-infarction left ventricular ejection fraction (LVEF), and time from ED presentation to PCI. We directly compared cases from two time intervals: January/February 2020 versus March/April 2020 (defined as 2 months before and after the COVID-19 outbreak). In a secondary analysis, we directly compared cases from March/April 2020 with patients from the same time interval in 2019. Results: From January to April 2020, 765 patients presented with acute chest pain to the ED. A dramatic reduction of ED presentations after compared to before the COVID-19 outbreak (31% relative reduction) was observed. Overall, 398 PCIs were performed, 220/398 PCIs (55.3%) before versus 178/398 PCIs (44.7%) after the outbreak. While numbers for NSTE-ACS and elective interventions declined by 21% and 31%, respectively, the number of STEMI cases remained stable. Time from cpo to ED presentation, post-infarction LVEF, and median door-to-balloon time remained unchanged. Conclusions: In contrast to previous reports, our findings do not confirm the dramatic drop in STEMI cases and interventions in northwestern Switzerland as observed in other regions and hospitals around the world.